ECHOING WASATHIYYAH: HOW INDONESIA EMERGES THE NORM OF MODERATE ISLAM IN INTERNATIONAL DISCOURSE (International Conference on Social and Islamic Studies, 2021)
The rise of negative discourse in the consequences of 9/11 put a strong pressureon Muslim-majority countries. The norm of terrorism or extremism is often attached to the idea of jihad which adhered to Islam. The implication of these diffusion is actually forcing many actors to restore Islam ideas that are not related to terrorism or extremism. Moderate Islam as an alternative norm finally tried to restore the previously diffused norm of Islam. Moderate Islam is then widely echoed in many countries. One of them is Indonesia, which has a Muslim-majority population. In this study, the researchers took the related literatures that describe, firstly, how far the norm of moderate Islam were raised in international discourseand then how far Indonesia was able to emerge the norm. Therefore, the researchers used a qualitative descriptive method. From the results of the study, the researchers noted that there were dynamic results in emerging the norm of moderate Islam, especially in Indonesia. The norm emergence of Wasathiyyah which contained in the norm of moderate Islam is considered to have succeed involving many community groups and government institutions in solidarity to emerge Wasathiyyah. The dynamics of emerging these norms in Indonesia cannot be separated from both domestic and international incentives. The researchers concluded that the norm of moderate Islam has reached a tipping point in international discourse which of course cannot be shattered from the influence of Muslim-majority countries such as Indonesia, despite the emergence of this norms was contested by extremism norm in the restoration of Islam norms. Thus, the researchers advocated for urging more actors, motives, and mechanisms to carry out the norm so that it can be absolutely legitimized in the international discourse.